Adverse effects of wastewater discharges in reproduction, energy budget, neuroendocrine and inflammation processes observed in marine clams Ruditapes philippinarum - Maranho, L. A.; Andre, C.; DelValls, T. A.; Gagne, F.; Martin-Diaz, M. L. (Elsevier B.V., 2015)
The present study investigated possible adverse outcomes in the marine clams Ruditapes philippinarum exposed to sediment affected by wastewater discharges at the Bay of Cadiz (SW, Spain). Six locations representing five cities were chosen for the sediment sampling during winter and summer seasons: P1 - Chiclana de la Frontera, P2 - Puerto Real, P3 - Cadiz, P4 and P5 - El Puerto de Santa Maria, P6 - Rota (reference site). Biochemical biomarkers were explored in clams after 14-days of exposure under controlled conditions, that included changes in cellular energy status (total lipids content TLP and mitochondrial electron transport activity MET), gametogenic activity (dopamine and ALP levels), metabolism of monoamines (monoamine oxidase activity - MAO), inflammation and spawning properties (cyclooxygenase activity - COX). Wastewater discharges induced energy budget alterations, as suggested by MET decrease (P4 and P5) and accumulation of To (P1, P2 and P3) in gonads. ALP levels (P1, P2 and P3), dopamine (P2) and COX activity (P1, P2, P3, P4 and P5) decreased in clams after the exposure to summer sediments. MAO increased in clams exposed to winter (P1 and P2) and summer (P3 and P4) sediments. Wastewater discharges composition changed between different seasons, mainly leading to oxidative stress, inflammation (COX activity and ALP levels) and spawning delay in summer. This study highlights the importance of considering reproduction of marine biota when assessing adverse effects of wastewater discharges. Continuous release of wastewater adequately threated or not, in aquatic ecosystems may culminate in adverse effects to the local benthic biota. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Seasonality; Ruditapes philippinarum; Wastewater discharges; Energy status; Neuroendocrine assessment; Impaired reproduction